Improving the Quality of Life and Social Development of the Donaranyick Community in Praksriracha District, Chainat Province - Tavornatvat, Staporn; Kitchainukoon, Pattaraporn (ASEAN Journal of Education, 2016)
The purposes of this research were: 1) To study the life quality of the Donaranyick Community. 2) To prepare the community plan for improving quality of life, 3) To prepare an action plan to guide improvements in the quality of life at the Don Aranyik Community, Phraek Si Racha Tambon, Sankhaburi Amphoe, Chainat. A purposive sampling method was used to collect a sample comprised of 60 households; community members assisted to derive the sample. The data collection was conducted by interview, questionnaire and AIC techniques. The data were analyzed by means of percentage, means and standard deviations. The results of the study were as follows: 1) Opportunities in education and professions of youth. In Sankhaburi Amphoe the educational system provides levels of study from kindergarten, primary, secondary and university levels. 2) Physical development of the community. Electricity, water supply, and roads are available; irrigation canals are also present for farmers.3) Solutions for poverty. Committees of local sectors and headman work with the local community, the temple, and educational institutions (i.e. Chandrakasem Rajabhat Center). 4) Accessibility services of the government. The decentralized local government works with the district administration and the local government organizations. 5) Accessibility services of local and government sectors. There are a lot of services available to support the local community. 6) Community participation by vocalizing opinions. “Yiam Ban Yam Yen”, which is the community forum, is held to criticize and plan the community plan every year. In addition, the community action plan was followed up by the addressing quality of life and community issues. The first priorities were the “Purposive Ground Project” in village 7 and the “Rice Drying Ground Project” in village 8. The action plan covered the meetings, public relations, as well as the elderly community activities. Furthermore, the “Purposive Ground Project” and the “Rice Drying Ground Project” were opened for the community members, Chandrakasem Rajabhat Center and Arunyig temple. The levels of satisfaction of the projects were at the high level for every item.